SP agar: media kultur alternatif untuk pertumbuhan bakteria (SP agar: alternative culture medium for the growth of bacteria) / Norazirah Mat Nayan, Sarina Mohamad and Nur Atiqah Abd Hadi - Mat Nayan, Norazirah; Mohamad, Sarina; Abd Hadi, Nur Atiqah (Universiti Teknologi MARA, 2020)
Media is essential to cultivate the growth of microorganism, especially for research studies. But, currently, the cost of microbiological media in the market is high. Besides, there is a problematic discharging issue of agriculture waste towards the environment and health. This study was carried out to develop and formulate an alternative medium that is costeffective from agriculture waste using Solanum tuberosum (potato) peels and Saccharum officinarum (sugarcane) bagasse as the main ingredients to support the growth of Gram-positive and Gram-negative bacteria. The bacteria (E.coli, K.pneumoniea, B.subtilis and S.epidermidis) with 0.5 McFarland of inoculum size inoculated on the different formulations of alternative media: a different ratio of potato peels and sugarcane bagasse respectively, which are Formulation A (1:1), Formulation B (1.5:0.5), and Formulation C (0.5:1.5). Nutrient agar used as a control medium. Each formulation added with 1.2 g agar, 1 mg NaCl and the pH adjusted to maintain at pH 7 by adding NaOH. The enumeration of each type of bacteria in all formulation media and control medium calculated in cfu/mL by using plate count technique. The results revealed that the highest enumeration of E.coli, K.pneumoniea, B.subtilis and S.epidermidis is in Formulation B (120.00±1.00, 99.33±1.52, 98.00±1.73 and 86.00±1.00 respectively) compared to Formulation A (38.30±1.53, 38.67±2.08, 20.67±2.08 and 44.33±3.05 respectively) and Formulation C (22.00±2.65, 39.00±2.00, 28.00±2.00 and 39.33±1.53 respectively). The findings showed that the potato peels and sugarcane bagasse have the potential to be used as sources of nutrient to formulate an alternative medium for culturing bacteria.